pK Determination. A Mean Field, Poisson-Boltzmann Approach - Neto, Augusto Agostinho [UNESP]; Drigo Filho, Elso [UNESP]; Fossey, Marcelo Andres [UNESP]; Neto, João Ruggiero [UNESP] (My University, 1999)
A model describing dissociation of monoprotonic acid and a method for the determination of its pK value are presented. The model is based on a mean field approximation. The Poisson-Boltzmann equation, adopting spherical symmetry, is numerically solved, and the solution of its linearized form is written. By use of the pH values of a dilution experiment of galacturonic acid as the entry data, the proposed method allowed estimation of the value of pK = 3.25 at a temperature of 25°C. Values for the complex dimensions and dissociation degree are calculated using experimental pH values for solution concentration values ranging from 0.1 to 60 mM. The present analysis leads to the conclusion that the Poisson-Boltzmann equation or its linear form is equally suited for the description of such systems.